2017
DOI: 10.3390/md15030083
|View full text |Cite
|
Sign up to set email alerts
|

An Extract from Shrimp Processing By-Products Protects SH-SY5Y Cells from Neurotoxicity Induced by Aβ25–35

Abstract: Increased evidence suggests that marine unsaturated fatty acids (FAs) can protect neurons from amyloid-β (Aβ)-induced neurodegeneration. Nuclear magnetic resonance (NMR), high performance liquid chromatography (HPLC) and gas chromatography (GC) assays showed that the acetone extract 4-2A obtained from shrimp Pandalus borealis industry processing wastes contained 67.19% monounsaturated FAs and 16.84% polyunsaturated FAs. The present study evaluated the anti-oxidative and anti-inflammatory effects of 4-2A in Aβ2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 69 publications
2
8
0
Order By: Relevance
“…It is not clear the reason why amyloid-β-induced cell death is independent on culture time. Recently, Zhang et al [ 39 ] also demonstrated that amyloid-β (20 μM)-induced cell death was higher at 24 h-culture than at 48 h-culture, which supports the present results. Further study should be performed to determine the mechanism of cell death by amyloid-β in neuronal cells using the different culture times.…”
Section: Discussionsupporting
confidence: 91%
“…It is not clear the reason why amyloid-β-induced cell death is independent on culture time. Recently, Zhang et al [ 39 ] also demonstrated that amyloid-β (20 μM)-induced cell death was higher at 24 h-culture than at 48 h-culture, which supports the present results. Further study should be performed to determine the mechanism of cell death by amyloid-β in neuronal cells using the different culture times.…”
Section: Discussionsupporting
confidence: 91%
“…We also found that treatment of amyloid peptides such as Aβ and Aβ 25-35 , nearly halved cell viability. The extent of sensitivity to amyloid peptides was similar to that of previously published values (9,11,12,13,15,18). These evidence suggests that the use of DMEM (supplemented with 10%FBS and antibiotics) is the best culture medium for both PC12 and SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 76%
“…As models of neurons, rat PC12 pheochromocytoma cells (6) and human SH-SY5Y neuroblastoma cells (7,8) have been used by many investigators to search for neuroprotective substances. However, the composition of the culture media they have used is quite different from researcher to researcher: RPMI1640 (differentiated PC12) (9, 10), RPMI (PC12) (11), DMEM (PC12) (12,13), DMEM (SH-SY5Y) (14), DMEM/Ham's F-12 (1:1) (SH-SY5Y) (15,16), MEM/F-12 (SY-SY5Y) (17) and DMEM/F-12 + non-essential amino acids (SH-SY5Y) (18), all supplemented with serum and antibiotics. It is not clear why the inclusion of F-12 and non-essential amino acids is necessary to culture SH-SY5Y cells.…”
mentioning
confidence: 99%
“…However, there was no uniformity in the culture condition of PC12 and SH-SY5Y cells in previous investigations. The culture media used was: Dulbecco’s modified Eagle’s medium (DMEM); the minimum essential medium (MEM); RPMI1640; a mixture of DMEM and Ham′s F12 (1:1); and, non-essential amino acids (NEAA), which were supplemented with fetal bovine serum (FBS), alone or together with, horse serum (HS) (column A in Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Differentiated and undifferentiated cells (column B), inoculated at different cell densities, were exposed to considerably different concentrations of neurotoxic agents (column C) in uncoated, collagen, or poly-lysine-coated plates ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%